Numerical Study of Laminar Free Convection Heat Transfer inside Porous Media -Filled Triangular Enclosure - Abood, Falah Assi (Basrah Journal for Engineering Sciences, 2011)
The natural convection heat transfer in a porous media filled and isothermally heated from the bottom wall of triangular enclosure is analyzed using finite element software package (FLEXPDE). Darcy’s law was used to write equations of porous media . The curved bottom wall shape, with Radii R= 0.8 , 1 and 1.5, was applied to a triangular enclosure. The boundary condition of the vertical wall is isothermal and of the inclined wall is adiabatic. The study was performed for different Rayleigh numbers (100 ≤ Ra ≤ 1000 ) and aspect ratios (0.4 ≤ AR ≤ 1 ) . Numerical results are presented in terms of streamlines, isotherms and Nusselt numbers. It was observed that heat transfer enhancement was formed with increasing Rayleigh number and aspect ratio . A comparison of the flow field and isotherm field is made with that obtained by [11], which revealed a good agreement .